A Rapid Approach for the Prediction of Seismic Ground Motion in Urban Areas. Issue 5 (October 2021) - Zhang, Xiaolong; Chen, Shaolin; Xu, Chong
Abstract: Rapid prediction of seismic ground motion can help with the assessment of seismic damage during earthquake emergencies. A numerical simulation is a powerful tool for achieving this end. However, existing methods for such simulations need a large number of seismic ground motion records. Moreover, their performance depends on large-scale computing resources, so they cannot meet the requirement of near real-time prediction of seismic ground motion. This paper proposes a rapid method for predicting seismic ground motion based on the 3D transfer function. This approach obtains the transfer function by solving the site seismic response under three impulse function excitations, calculated by different pre-event 3D physics-based numerical simulations. The approach only needs one seismic record in the study area and can quickly yield the seismic ground motion of the whole study area. The proposed approach is verified by modeling site response to an assumed earthquake, which was affected by the 2008 Wenchuan M7.9 event. The results confirm that the proposed method has sufficient accuracy in near real-time prediction of seismic ground motion.